PENGARUH PEMBERIAN VIDEO EDUKASI GEMPA BUMI TERHADAP KESIAPSIAGAAN BENCANA PADA MAHASISWA ASRAMA UNISA YOGYAKARTA - Muhammad Hafidh Zidan; Endah Tri Wulandari (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
Disasters are events that threaten and disrupt people's lives. Earthquakes are serious natural disasters in certain areas, including the Special Region of Yogyakarta which is located in areas prone to earthquakes. The lack of knowledge about earthquake preparedness shows the urgency of improving disaster preparedness, especially for students who have just settled in Yogyakarta. One way to improve disaster preparedness is to provide education about the disaster, the use of educational videos can make it easier to provide education about disasters because videos can provide interesting and easy-to-understand explanations. This study was conducted to determine the effect of providing earthquake education videos on disaster preparedness in students of the Unisa Yogyakarta Dormitory. The type of research carried out is quantitative research with an experimental research design using one group pretest and posttest design. The sampling technique used a total sampling with a total of 35 respondents from the Unisa Yogyakarta Dormitory. The results of the test of the effect of providing earthquake education videos on disaster preparedness in Unisa Yogyakarta Dormitory students using the wilcoxon test obtained a significant p-value of 0.000 < 0.05, so that there was an effect of providing earthquake education videos on disaster preparedness in Unisa Yogyakarta Dormitory students. Researchers can then consider making an educational video about the earthquake and patenting the video and working with the campus to make the best use of it.